USE OF GLYCEROL AT 8% CONCENTRATION DURING CYROPRESERVATION IS OPTIMAL FOR THE POST-THAW QUALITY OF CAUDA EPIDIDYMAL SPERMATOZOA OF RAM - AHMED, T; ISLAM, R (The Indian Journal of Animal Reproduction, 2016)
The cauda epididymal spermatozoa of ram recovered using incision method and showing progressive motility ≥70% were pooled and divided into aliquots before extension in Tris-Citric acid-Fructose-Egg yolk extender using glycerol at 4% (G4), 6% (G6) and 8% (G8) concentration as cryoprotectant. At post-thaw stage, the sperm motility was higher (P<0.05) for G8 than G4. At pre-freeze stage, the hypoosmotic swelling test (HOST) reacted spermatozoa were higher (P<0.05) for G8 and G6 than G4. However, at post-thaw stage, the HOST reacted spermatozoa were higher (P<0.05) for G8 than both G6 and G4. In conclusion, 8% glycerol provides better sperm motility and sperm membrane integrity and is recommended for the freezing of ram cauda epididymal spermatozoa